THOUGHTS OF CHINESE SCHOLARS ON KANGJU CULTURE (CONTINUATION) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the culture of the state of Kangju on the basis of historical data from Chinese written sources and archaeological excavations in Central Asia, the location of the Kangju culture, their names in Chinese sources, comparative finds of various cultures and their influences are revealed.